Evaluation of the Effectiveness of Irrigation Water Distribution in Range Weir Irrigation Areas Using the Water Balance Method - M.Fahmi Husein; Awliya Tribhuawana (Riviera Publishing, 2026)
Irrigation systems play an essential role in supporting agricultural productivity and food security, particularly in areas where water availability is influenced by seasonal variability and infrastructure conditions. The Rentang Irrigation Area in West Java is one of the largest irrigation systems in Indonesia and contributes significantly to rice production; however, challenges related to uneven water distribution, water losses, and fluctuating water availability affect irrigation performance. This study aims to evaluate the effectiveness of irrigation water distribution in the Rentang Weir Irrigation Area using the Water Balance method. The research employed a quantitative evaluative approach by analyzing irrigation water availability and demand. Data collected included river discharge, rainfall, climatological parameters, cropping patterns, and irrigation network conditions. Water availability was determined using dependable discharge analysis, while irrigation water requirements were calculated based on the FAO-56 Penman–Monteith method and Indonesian Irrigation Planning Standard (KP-01). The results indicate that water availability varies significantly according to seasonal conditions, with water surpluses occurring during the rainy season and deficits appearing during the dry season. The effectiveness of water distribution is influenced by the balance between supply and demand, irrigation network conditions, and water losses caused by seepage, evaporation, leakage, and sedimentation. The Water Balance method provides an effective evaluation framework for assessing irrigation performance and supporting sustainable water resource management. This study recommends optimizing planting patterns and improving irrigation operation and maintenance to enhance water distribution efficiency in the Rentang Irrigation Area